Methadone-Induced Toxic Leukoencephalopathy: MR Imaging and MR Proton Spectroscopy Findings - Salgado, R.A.; Jorens, P.G.; Baar, I.; Cras, P.; Hans, G.; Parizel, P.M. (American Journal of Neuroradiology, 2010)
SUMMARY: We report the clinical, MR imaging, and proton MR spectroscopy findings in a middle-aged woman with proved methadone-induced toxic leukoencephalopathy. The imaging characteristics of this unusual condition have been reported only rarely in the medical literature. We show that the imaging findings in methadone-induced toxic leukoencephalopathy are similar, though not identical, to previously reported cases of neurologic deterioration due to heroin inhalation. ChocholineCrcreatineFLAIRfluid-attenuated inversion recoveryNAAN-acetylaspartate